The impacts of milk butter from iraqi-bred cows fed on a diet mixed with fenugreek seed on the lipid profile of wistar rats in al-diwaniyah city, iraq (World Journal of Current Medical and Pharmaceutical Research, 2023)
The current study was carried out to study the impacts of milk butter from Iraqi-bred cows fed on a diet mixed with fenugreek seed on the lipid profile of Wistar ratsin Al-Diwaniyah City, Iraq. The experiment contained the recruitment of 10 lactating locally-bred cows (LLBCs) fed with 12.5gm/animal/day for 24months of soaked fenugreek seeds (SFSs), SFS group. As a cow control (CC) group, 10 LLBCs were used with no treatment. After the end of this experiment, the milk was utilized to produce butter. Then, the SFS-originated butter (SFSB) was orally-administered to 10 rats at 0.08mg/kg daily for 30 days, SFSB group. For the rat control (RC) group, 10 rats were orally-administered with CC-originated butter (CCB) at 0.08mg/kg daily for 30 days, CCB group. After the end of the rat experiment, the body weight and serum profile of lipids of rats for both SFSB and CCB groups were measured. The result showed that the oral supply of the butter from SFS cows induced potentially (p˂0.05) increased in the HDL levels in the SFSB rats. In addition, the LDL and VLDL from the same rats revealed no significant (p˃0.05) changes after using the butter originated from the cows treated with SFS. Significant (p˂0.05) elevations were recorded in the levels of TC, TG, and weights in the rats treated with the butter produced from the SFS cow milk. The study concludes that feeding cows with fenugreek seeds has successful impacts in increasing the levels of HDL “good lipid” and decreasing the levels of LDL and VLDL “bad lipids” in the rats treated orally with butter produced from these cows.